Co-Existence of Darier Disease and Acrokeratosis Verruciformis of HOPF - Imtiaz, Sania; Sadaf Ahmed Asim; Sharmeen Nasir (Journal of Pakistan Association of Dermatologists, 2025)
Darier disease is an uncommon hereditary condit-ion with a a prevalence of 1 case per 100,000 people and characterized by aberrant keratinization pat-terns, with an autosomal dominant mode of inheritance. It affects the seborrheic areas as well as the palms, nails, and oral mucosa. The lesions are firm, rather greasy, crusted papules that are skin-coloured to yellow-brown.1 Acrokeratosis verruciformis of Hopf is an uncommon autosomal genodermatosis, which is a hereditary skin disorder initially documented by Hopf in 1931. It is distinguished by the existence of flat, skin to reddish brown papules located on the dorsal surface of the hands and feet. These papules may also extend to the forearms, knees and elbows.2 In this particular case report, our objective was to thoroughly examine the clinical and histopa-thological findings of these two diseases, conside-ring the most recent literature available. Case Report A 17-year-old girl presented with itchy skin-coloured to brownish papules on neck, axilla, umbilicus, trunk, hands, and feet since the age of 6 years. The patient had skin-coloured papules that initially first appeared over the dorsa of hands and feet followed by brownish to violaceous papules appearing on the axilla, neck and trunk. On dermatological examination: multiple, small, skin-coloured, flat-topped, papules were present over dorsa of hands and feet (Figure 1). Multiple, slightly violaceous, flat topped, papules were present over the axilla, inguinal crease, umbilicus, face upper chest, back, and abdomen (Fig. 2, 3, 4). No scalp, genital and oral mucosal lesions were observed. Nail examination revealed V-shaped nick on the nail of middle finger of the right hand (Fig. 5). She complained of aggravation of these lesions which was more prominent during the summer. Systemic physical examination and routine haematological and biochemical workup were within the normal limits